Rammed earth walls repair by earth-based mortars: The adequacy to assess effectiveness - Gomes, Maria (2019)
Repairs in rammed earth walls are often necessary mainly because of degradation occurring during the life time of a building with continuous environmental exposure. The defects that arise in the walls are generally associated with loss of its thickness, on the surface or in greater depth. They must be repaired with a mortar technically efficient and compatible with the rammed earth, to ensure protection and, as possible, long-term durability. The present study describes and discusses the adequacy of earth-based mortars to repair unstabilized rammed earth walls and the behaviour of the systems rammed walls-earth repair mortars when subjected to accelerated aging tests by wetting-drying cycles. Even under aggressive capillarity tests, the results observed corroborate that unstabilized earth repair mortars behave better in comparison to similar mortars with additions of low amounts of different inorganic binders.